Preparation method of functional ceramsite, high-ZT-value concrete and preparation method of high-ZT-value concrete
By preparing functional ceramite and conductive polyaniline-carbon nanotube composites, the problem of difficult to achieve high ZT values in concrete is solved, and the thermoelectric performance improvement and mechanical performance maintenance of concrete is achieved.
Patent Information
- Application Number
- CN202411980045.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to achieve high ZT values in concrete, mainly due to the limited volume of cement slurry, the limited amount of functional material and the lack of functional aggregates, which makes it difficult to improve the thermoelectric performance.
By preparing functional ceratops and using magnetite in high-iron fly ash for roasting and magnetic separation, functional ceratops with high magnetic properties and excellent thermoelectric properties are prepared, and they work in concert with conductive polyaniline-carbon nanotube composite materials to improve the thermoelectric properties of concrete.
The functional synergy between aggregate and cement slurry in concrete is realized, the thermoelectric coefficient, conductivity and ZT value of concrete are improved, while maintaining the mechanical properties of concrete.
Smart Images

Figure BDA0005221330350000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a method for preparing functional ceramsite, high ZT value concrete and a preparation method thereof. Background Art
[0002] The ZT value is a coefficient that comprehensively measures the performance of thermoelectric materials. The larger the ZT value of thermoelectric materials, the better the thermoelectric performance of the materials. In the prior art, when preparing high ZT value functional concrete, non-metallic materials such as carbon fiber, carbon nanotubes, graphite, carbon black, or metal materials such as steel fiber and steel slag are generally added to the cement paste. However, due to the limited volume proportion of cement paste in concrete, the amount of metal or non-metal functional materials is also very limited. If the amount of these functional materials is increased, the mechanical properties of concrete will be greatly reduced. In addition, the aggregates that occupy a large volume ratio in concrete do not have corresponding functions, and even block the passage of the functional phase in the cement paste. In addition, to achieve a higher ZT value, a higher thermoelectric coefficient, a higher electrical conductivity and a lower thermal conductivity are required, and the three will affect each other, so it is more difficult to prepare functional concrete with a high ZT value. Summary of the invention
[0003] In order to solve the problem that high ZT of concrete is difficult to achieve in the prior art, the present invention provides a preparation method of functional ceramsite, high ZT value concrete and a preparation method thereof, wherein aggregates occupying a larger volume ratio in concrete are endowed with corresponding functions, and the prepared functional ceramsite has high cylinder compressive strength and strong Seebeck effect, and the functional ceramsite is synergistically combined with functional cement paste to improve the relevant properties of concrete, thereby realizing the preparation of high ZT value concrete.
[0004] The technical objectives of the present invention are achieved through the following technical solutions:
[0005] A method for preparing functional ceramsite, comprising:
[0006] S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite;
[0007] S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D;
[0008] S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash;
[0009] S4, granulating the high magnetic fly ash to form functional ceramsite raw balls E;
[0010] S5, calcining the functional ceramsite green ball E under an inert atmosphere, including three stages:
[0011] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;
[0012] In the second stage, the sintering temperature was 1100°C and the sintering time was 20 min;
[0013] In the third stage, rapid cooling for 15 min until the temperature drops to room temperature, and crude functional ceramsite F is obtained;
[0014] S6. Screening the crude functional ceramsite F to obtain functional ceramsite, the apparent density of which is 2000-2300 kg / m 3 , cylinder pressure strength is 6~10MPa, and particle size is 5~20mm.
[0015] Furthermore, the Fe2O3 content in the high iron fly ash is 14% to 20%, the SiO2 content is 45% to 54%, the Al2O3 content is 25% to 30%, the Na2O content is 0.5% to 1%, the K2O content is 0.5% to 1%, the CaO content is 1% to 4%, the MgO content is 0.5% to 3%, and the residual carbon content is 4% to 6%.
[0016] Furthermore, the mass ratio of the calcined fly ash A to water is 1:9 to 1:4.
[0017] Furthermore, the content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.
[0018] The present invention also provides a high ZT value structural functional integrated concrete, which comprises, by mass ratio, 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 850-880 parts of functional ceramsite, 1200-1400 parts of magnetite sand, 0.4-1 part of conductive polyaniline-carbon nanotube composite material, 4-6 parts of water reducer, and 160-170 parts of water. The low magnetic fly ash and the functional ceramsite are prepared by the above-mentioned preparation method of the functional ceramsite, and the conductive polyaniline-carbon nanotube composite material is prepared by polymerizing aniline on carbon nanotubes by using ammonium persulfate as an initiator.
[0019] Furthermore, the particle size of the magnetite sand is 315 μm to 2.50 mm.
[0020] Furthermore, the water reducer is a high-performance polycarboxylate water reducer.
[0021] The present invention also provides a method for preparing high ZT value structural-functional integrated concrete, the method comprising:
[0022] S1. Take 850-880 parts of functional ceramsite and soak it in water for 24 hours, and weigh it to determine the water absorption of the functional ceramsite;
[0023] S2, preparing a conductive polyaniline-carbon nanotube composite material, taking 0.4-1 parts of the conductive polyaniline-carbon nanotube composite material according to the mass fraction ratio and ultrasonically dispersing it in 20-40 parts of water for 30-60 minutes to obtain an ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K for standby use;
[0024] S3, taking 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 850-880 parts of functional ceramsite after water absorption, and 1200-1400 parts of magnetite sand, stirring and mixing them evenly to obtain dry material I;
[0025] S4, take 4 to 6 parts of water reducing agent, pour it into the remaining water and stir it evenly, add it into the dry material I and mix it evenly to obtain slurry J;
[0026] S5. Add the ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K into the slurry J and stir evenly to obtain a high ZT value structural functional integrated concrete.
[0027] Furthermore, in step S2, the method for preparing the conductive polyaniline-carbon nanotube composite material includes:
[0028] S21, ultrasonically dispersing the carbon nanotubes in a 0.5 mol / L H2SO4 solution at a ratio of 1 g / 40 ml;
[0029] S22, adding aniline to the solution obtained in step S21 at a ratio of 1 g / 20 ml and stirring for 30 min;
[0030] S23, adding 0.025 mol / L ammonium persulfate solution to the solution prepared in step S22 at a volume ratio of 1:10, and stirring in an ice bath for 3 h;
[0031] S24, filtering, washing and drying the product obtained in step S23 to obtain a conductive polyaniline-carbon nanotube composite material.
[0032] Further, in step S21, the purity of the carbon nanotubes is greater than 95 wt%, the inner diameter is 3-5 nm, the outer diameter is 8-15 nm, the length is 3-12 μm, and the specific surface area is greater than 233 m2 / g.
[0033] Further, in step S22, the aniline is analytically pure aniline.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The high ZT value structural functional integrated concrete of the present invention realizes the functional synergy of aggregate and cement paste, the functional synergy of inorganic materials and organic materials, and the functional synergy of metal oxides and non-metallic carbon materials. The functional ceramsite as coarse aggregate contains a large amount of magnetite, and is matched with fine aggregate magnetite sand, which has high thermoelectric coefficient and high electrical conductivity; the conductive polyaniline-carbon nanotube composite material added to the cement paste takes advantage of the low thermal conductivity of high molecular organic polymers, and gives full play to the excellent semiconductor properties and thermoelectric properties of carbon nanomaterials, so that the prepared concrete has high thermoelectric coefficient, high electrical conductivity and low thermal conductivity, thereby achieving a high ZT value of concrete.
[0036] 2. The present invention uses ammonium persulfate to initiate in-situ polymerization of aniline on carbon nanotubes to form a conductive polyaniline-carbon nanotube composite material, and in view of the problem that it is difficult to disperse, ultrasonic dispersion and dispersant are combined to make the carbon nanotubes uniformly dispersed in cement paste. On the one hand, the polycarboxylate water reducer plays the role of a common water reducer, and on the other hand, it is an anionic surfactant that can promote the dispersion of carbon nanotubes.
[0037] 3. The present invention selects fly ash with high iron content and utilizes reduction-magnetic separation-inert atmosphere sintering process to reduce the hematite in the high-iron fly ash to highly magnetic magnetite by the residual carbon in the fly ash. No additional reducing agent is needed. During the sintering process of the ceramsite, the magnetite is protected by the inert atmosphere to prevent the sintering of the magnetite into hematite or iron. As a result, the functional ceramsite obtained by sintering contains a large amount of magnetite, thereby improving the thermoelectric properties of the coarse aggregate.
[0038] 4. The present invention improves the strength of cement paste and the functionality of ceramsite by transferring the "iron" in fly ash, which is detrimental to the mechanical properties of concrete, from cement paste to ceramsite. On the one hand, most of the iron oxides are removed from the low-magnetic fly ash in the cement paste, the iron content is reduced, and the content of active silicon-aluminum substances is increased, thereby increasing the volcanic ash activity of fly ash and thus improving the strength of concrete; on the other hand, the functional ceramsite has a high content of magnetite, which improves the thermoelectric properties of ceramsite, thereby improving the functionality of the prepared concrete. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments:
[0040] Example 1
[0041] 1. A method for preparing functional ceramsite, characterized in that it comprises:
[0042] S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite;
[0043] Among them, the Fe2O3 content in high iron fly ash is 14% to 20%, the SiO2 content is 45% to 54%, the Al2O content is 25% to 30%, the Na2O content is 0.5% to 1%, the K2O content is 0.5% to 1%, the CaO content is 1% to 4%, the MgO content is 0.5% to 3%, and the residual carbon content is 4% to 6%.
[0044] In this stage, the hematite in the high iron fly ash A undergoes a reduction reaction at high temperature, and the reaction process is as follows:
[0045] 2C+O2=2CO
[0046] 3Fe2O3+CO=2Fe3O4+CO2
[0047] S2. Disperse the calcined fly ash A in water at a mass ratio of 1:9 to 1:4. In this embodiment, the mass ratio of the calcined fly ash A to water is 1:5 to obtain a calcined fly ash solution B. Separate the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D.
[0048] More specifically, the process of separating magnetic substances is as follows:
[0049] Step S21, stirring the roasted fly ash solution B by a magnetic bar with a magnetic induction intensity of 1T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar, and the magnetic substance on the surface of the magnetic bar is collected for later use; repeating the above process until the surface of the magnetic bar with a magnetic induction intensity of 1T is no longer adsorbed with magnetic substances;
[0050] Step S22, stirring the roasted fly ash solution B after the treatment in the above step S21 by a magnetic bar with a magnetic induction intensity of 1.2T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar with a magnetic induction intensity of 1.2T, collecting the magnetic substance on the surface of the magnetic bar with a magnetic induction intensity of 1.2T for later use, and repeating the operation until the surface of the magnetic bar with a magnetic induction intensity of 1.2T is no longer adsorbed with magnetic substances;
[0051] Step S23, the collected magnetic substances are mixed to obtain wet high magnetic fly ash C, and the roasted fly ash solution B is processed in step S22 to obtain low magnetic fly ash solution D.
[0052] S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash; during drying, drying in an oven at a drying temperature of 60°C.
[0053] More specifically, the content of Fe2O3 in high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in low magnetic fly ash is 2% to 6%.
[0054] S4, granulating the high magnetic fly ash to form functional ceramsite raw balls E. During granulation, the high magnetic fly ash is placed on a disc of a disc ball making machine, and the disc is rotated horizontally while water is sprinkled until the high magnetic fly ash is rolled into a ball on the disc, and the functional ceramsite raw balls E are obtained after drying.
[0055] S5, calcining the functional ceramsite green ball E under argon protection, including three stages:
[0056] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;
[0057] In the second stage, the sintering temperature was 1100°C and the sintering time was 20 min;
[0058] In the third stage, rapid cooling for 15 min until the temperature drops to room temperature, and crude functional ceramsite F is obtained;
[0059] In the above sintering process, argon as an inert atmosphere prevents the magnetite in the functional ceramsite green ball E from being reduced or oxidized, so that a large amount of magnetite is retained in the ceramsite after sintering.
[0060] S6. Screening the crude functional ceramsite F to obtain functional ceramsite, the apparent density of which is 2000-2300 kg / m 3 , cylinder pressure strength is 6~10MPa, and particle size is 5~20mm.
[0061] Example 2
[0062] A high ZT value structural functional integrated concrete comprises, by mass ratio: 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 862 parts of functional ceramsite, 1326 parts of magnetite sand, 0.7 parts of conductive polyaniline-carbon nanotube composite material, 5 parts of water reducer, 165 parts of water, the low magnetic fly ash and functional ceramsite are prepared by the method of Example 1, and the conductive polyaniline-carbon nanotube composite material is prepared by polymerizing aniline on carbon nanotubes using ammonium persulfate as an initiator. The particle size of the magnetite sand is 315 μm to 2.50 mm, and the water reducer is a high-performance polycarboxylate water reducer.
[0063] The preparation process of the above-mentioned high ZT value structural functional integrated concrete is as follows:
[0064] S1. Take 862 parts of functional ceramsite and soak them in water for 24 hours, and weigh them to determine the water absorption of the functional ceramsite;
[0065] S2, preparing a conductive polyaniline-carbon nanotube composite material, taking 0.7 parts of the conductive polyaniline-carbon nanotube composite material according to the mass fraction ratio and ultrasonically dispersing it in 30 parts of water for 30 minutes to obtain an ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K for later use;
[0066] S3, take 215 parts of cement, 62 parts of low magnetic fly ash, 93 parts of mineral powder, 862 parts of functional ceramsite after water absorption, and 1326 parts of magnetite sand, stir and mix them evenly to obtain dry material I;
[0067] S4, after deducting the water absorption of the functional ceramsite and the water consumption of the ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K, 5 parts of the water reducer are poured into the remaining water and stirred evenly, and then added into the dry material I and mixed and stirred evenly to obtain slurry J;
[0068] S5. Add the ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K into the slurry J and stir evenly to obtain a high ZT value structural functional integrated concrete.
[0069] More specifically, in step S2, the method for preparing the conductive polyaniline-carbon nanotube composite material includes:
[0070] S21, ultrasonically dispersing the carbon nanotubes in a 0.5 mol / L H2SO4 solution at a ratio of 1 g / 40 ml, wherein the H2SO4 solution provides an acidic environment for subsequent processes;
[0071] The purity of the carbon nanotubes is greater than 95 wt%, the inner diameter is 3 to 5 nm, the outer diameter is 8 to 15 nm, the length is 3 to 12 μm, and the specific surface area is greater than 233 m2 / g.
[0072] S22, adding aniline to the solution prepared in step S21 at a ratio of 1 g / 20 ml and stirring for 30 min, wherein the aniline is analytically pure aniline.
[0073] S23, adding 0.025 mol / L ammonium persulfate solution to the solution prepared in step S22 at a volume ratio of 1:10, and stirring in an ice bath for 3 hours. Ammonium persulfate oxidizes aniline, and in-situ polymerization occurs under the acidic condition of H2SO4 solution to generate polyaniline, which polymerizes on the surface of the carbon nanotubes.
[0074] S24, filtering, washing and drying the product obtained in step S23 to obtain a conductive polyaniline-carbon nanotube composite material.
[0075] The high ZT value structural functional integrated concrete prepared by the method of the above Example 2 was tested for compressive strength and ZT value. The test results are shown in the following table:
[0076] Test items Compressive strength(MPa) ZT value Example 2 38.5 4.02×10
[0077] It can be concluded from the test results in the above table that the high ZT value structural functional integrated concrete prepared in Example 2 has high compressive strength and high ZT value. The magnetite contained in the functional ceramsite as coarse aggregate, the magnetite sand as fine aggregate and the conductive polyaniline-carbon nanotube composite material in the cement paste work synergistically to improve the ZT value of the concrete and the thermoelectric conversion efficiency of the concrete.
[0078] The ZT value in the prior art needs to be calculated comprehensively as follows:
[0079]
[0080] In the above formula, k is thermal conductivity, σ is electrical conductivity, S is Seebeck coefficient, and T is absolute temperature.
[0081] It should be noted that in this application, the letters in the calcined fly ash A, calcined fly ash solution B, wet high magnetic fly ash C, low magnetic fly ash solution D, functional ceramsite raw balls E, crude functional ceramsite F, dry material I, slurry J and ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K have no special limiting meaning and are only used to distinguish substances and materials.
[0082] This embodiment is only a further explanation of the present invention, not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it will be protected by the patent law.
Claims
1. A method for preparing functional ceramsite, characterized in that: include: S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite; S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D; S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash; S4, granulating the high magnetic fly ash to form functional ceramsite raw balls E; S5, calcining the functional ceramsite green ball E under an inert atmosphere, including three stages: In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes; In the second stage, the sintering temperature was 1100°C and the sintering time was 20 min; In the third stage, rapid cooling for 15 min until the temperature drops to room temperature, and crude functional ceramsite F is obtained; S6, screening the crude functional ceramsite F to obtain functional ceramsite, wherein the apparent density of the functional ceramsite is 2000-2300 kg / m 3 , cylinder pressure strength is 6~10MPa, and particle size is 5~20mm.
2. The method for preparing a functional ceramsite according to claim 1, characterized in that: The high iron fly ash has a Fe2O3 content of 14% to 20%, a SiO2 content of 45% to 54%, an Al2O3 content of 25% to 30%, a Na2O content of 0.5% to 1%, a K2O content of 0.5% to 1%, a CaO content of 1% to 4%, a MgO content of 0.5% to 3%, and a residual carbon content of 4% to 6%.
3. The method for preparing a functional ceramsite according to claim 1, characterized in that: The mass ratio of the calcined fly ash A to water is 1:9 to 1:
4.
4. The method for preparing a functional ceramsite according to claim 1, characterized in that: The content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.
5. A high ZT value structural functional integrated concrete, characterized in that: The composition comprises, by weight: 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 850-880 parts of functional ceramsite, 1200-1400 parts of magnetite, 0.4-1 parts of conductive polyaniline-carbon nanotube composite material, 4-6 parts of water reducer, and 160-170 parts of water. The low magnetic fly ash and functional ceramsite are prepared by the method according to any one of claims 1 to 4. The conductive polyaniline-carbon nanotube composite material is prepared by polymerizing aniline on carbon nanotubes using ammonium persulfate as an initiator.
6. The high ZT value structural functional integrated concrete according to claim 5, characterized in that: The particle size of the magnetite sand is 315 μm to 2.50 mm.
7. The high ZT value structural functional integrated concrete according to claim 5, characterized in that: The water reducer is a high-performance polycarboxylate water reducer.
8. A method for preparing high ZT value structural functional integrated concrete as claimed in claim 5, characterized in that: The method includes: S1. Take 850-880 parts of functional ceramsite and soak it in water for 24 hours, and weigh it to determine the water absorption of the functional ceramsite; S2, preparing a conductive polyaniline-carbon nanotube composite material, taking 0.4-1 parts of the conductive polyaniline-carbon nanotube composite material according to the mass fraction ratio and ultrasonically dispersing it in 20-40 parts of water for 30-60 minutes to obtain an ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K for standby use; S3, taking 200-220 parts of cement, 60-70 parts of low magnetic fly ash, 90-100 parts of mineral powder, 850-880 parts of functional ceramsite after water absorption, and 1200-1400 parts of magnetite sand, stirring and mixing them evenly to obtain dry material I; S4, take 4 to 6 parts of water reducing agent, pour it into the remaining water and stir it evenly, add it into the dry material I and mix it evenly to obtain slurry J; S5. Add the ultrasonically dispersed conductive polyaniline-carbon nanotube mixed solution K into the slurry J and stir evenly to obtain a high ZT value structural functional integrated concrete.
9. The method for preparing a high ZT value structural-functional integrated concrete according to claim 8, characterized in that: In step S2, the method for preparing the conductive polyaniline-carbon nanotube composite material includes: S21, ultrasonically dispersing the carbon nanotubes in a 0.5 mol / L H2SO4 solution at a ratio of 1 g / 40 ml; S22, adding aniline to the solution obtained in step S21 at a ratio of 1 g / 20 ml and stirring for 30 min; S23, adding 0.025 mol / L ammonium persulfate solution to the solution prepared in step S22 at a volume ratio of 1:10, and stirring in an ice bath for 3 h; S24, filtering, washing and drying the product obtained in step S23 to obtain a conductive polyaniline-carbon nanotube composite material.
10. The method for preparing a high ZT value structural-functional integrated concrete according to claim 9, characterized in that: In the step S21, the purity of the carbon nanotubes is greater than 95 wt%, the inner diameter is 3-5 nm, the outer diameter is 8-15 nm, the length is 3-12 μm, and the specific surface area is greater than 233 m2 / g.
11. The method for preparing a high ZT value structural-functional integrated concrete according to claim 9, characterized in that: In step S22, the aniline is analytically pure aniline.
Citation Information
Patent Citations
Coal ash micelle with high magnetic response and preparation method and application thereof
CN102895956A
Magnetic fly ash ceramsite and preparation method thereof
CN104261553A
Manufacturing method and apparatus for novel biomagnetic ceramsite filler for water treatment
JP6555770B1
Methods of making fly-ash aggregate
KR1020110032968A
Method for preparing ceramsite by using municipal sludge as raw material
US20200048147A1